Hemorrhagic cystitis caused by extraintestinal pathogenic Escherichia coli in a dog (Canis lupus familiaris) - Troncellito, Agustina; Fresneda, Karina C.; Moore, Janet D.; DebRoy, Chitrita; Escobar, Carolina; Carvallo, Francisco R. (Brazilian Journal of Veterinary Pathology, 2019)
Escherichia coli strains that are able to colonize outside of the gastrointestinal tract are classified as extraintestinal pathogenic E. coli (ExpEC). A 6.5 female German shepherd dog with history of fever and hematuria was submitted for necropsy. Extensive transmural hemorrhagic cystitis with necrotizing vasculitis was identified in the urinary bladder. Multifocal thrombosis and intralesional bacteria were seen in the kidneys, liver, spleen and brain. E. coli O88:H4 was isolated in pure culture from the urinary bladder and other organs. This strain carried the virulence genes cnf-1, sfa, fim, hlyD and PapGIII which are associated with ExpEC strains.